THE VALIDITY AND PRACTICALITY OF THE CHEMISTRY LEARNING DEVICE BY USING STEM-PJBL MODEL - Suwadarma, K W; Sudiatmika, A A I A R; Suja, I W (Jurnal Imiah Pendidikan dan Pembelajaran, 2020)
The purpose of this research is to improve the Motivation and Learning Achievement of Singaraja Vocational High School 2 Students in the 2016/2017 Academic Year with Discovery Learning Learning Model. This research is classroom action research. The research subjects that will be used as the research are students in class XI of Catering 4 Singaraja 2 nd Vocational School 2016/2017 in the year of 41 people 25 people and 16 women while the object of research is student motivation and learning achievement. Data on student learning achievements collected at the end of each cycle using the test. Data on learning motivation were collected using learning motivation questionnaire sheets in the form of questionnaires. Data analysis used in this study used descriptive data analysis. Based on the data analysis conducted, it can be concluded that the implementation of the Discovery Learning model can increase motivation and learning achievement of Crafts and Entrepreneurship in class XI 1 students of SMK Negeri 2 Singaraja Academic Year 2016/2017.Keywords: Learning Devices, STEM-PJBL Model, Chemistry, Validity and Practicality